1982
DOI: 10.1029/jc087ic13p11229
|View full text |Cite
|
Sign up to set email alerts
|

A model for microwave emission from vegetation‐covered fields

Abstract: A radiative transfer model for simulating the measured brightness temperatures over vegetation‐covered fields is studied. The model treats the vegetation as a uniform layer, or canopy, with a constant temperature over a moist soil which emits polarized microwave radiation. The equation of radiative transfer is solved analytically subject to boundary conditions at the soil surface and canopy top. Scattering by the vegetation is primarily in the forward direction and given by a single scattering albedo ω*. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
332
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(334 citation statements)
references
References 15 publications
1
332
0
1
Order By: Relevance
“…For L-band, it has been shown that c = 0.12 [21]. The T values for C-band are 2 to 5 times larger than those for L-band.…”
Section: The Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For L-band, it has been shown that c = 0.12 [21]. The T values for C-band are 2 to 5 times larger than those for L-band.…”
Section: The Resultsmentioning
confidence: 95%
“…A previous investigation [21] shows that T is proportional to the vegetation canopy water content W (in kg/m 2 ), and that it can be given by the simple form,…”
Section: The Resultsmentioning
confidence: 99%
“…Once the weighting factor η p and the brightness temperatures of the surrounding area TB O,p are known, the brightness temperatures emitted from the observed soil-vegetation scene TB S,p can be derived from the L-band radiometer measurements using Equation (1). The brightness temperatures emitted from the soil-vegetation scene (TB S,p ) were simulated using a simple radiative transfer (RT) model, referred to as the tau-omega (τ-ω) model [15], which describes Remote Sens. 2018, 10, 304 7 of 18 the emission contributions of soil and vegetation.…”
Section: Radiative Transfer Modelmentioning
confidence: 99%
“…During recent years, the effect of soil organic matter on passive L-band microwave signals has also been studied in the context of the ESA SMOSHiLat project [13]. L-band radiometer algorithms for soil moisture retrieval are based on the use of a radiative transfer (RT) model [12,14,15] and a dielectric mixing model [16][17][18] to derive soil moisture information from brightness temperature observations. The listed dielectric mixing models were developed for mineral soils and no information on organic matter content can be accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can be shown [7] that if a 20% polarization mixing is assumed for the L-band case in Figure 2, the calculated T V value at 70 0 would be 265K, instead of 290K as shown in Figure 2. However, the assumption of polarization mixing is not employed in this study, because other uncertainties may exist.…”
Section: -4mentioning
confidence: 99%